MYOB Accounting Information System Analysis at PT. Lembang Abadi Indah - Irma Suryani; Dedeh Kurniawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The background of this research is the need for quality financial reports. This research aims to determine how the implementation of accounting information system in PT. Lembang Abadi Indah based MYOB. With the use of MYOB software application for accounting information System the company can improve the quality of accounting information in generating relevant financial statements.  The methods used in research are qualitative approaches. Design research is a qualitative dexriptif. The source of data obtained from this research is from primary data on primary data collection conducted through observation and interviews with the authorities. In this research, the secondary data sources used by researchers are sources related to the research object can be an accounting information system based on MYOB Accounting V13 that has been implemented in PT. Lembang Abadi Indah. The implementation of an accounting information system based on MYOB at PT. Lembang Abadi Indah is already running well, MYOB provides the relevance of information in supporting business process, including it is presented in a timely, accurate, consistent, usable and complete. With the application of MYOB accounting information obtained by the company become more accurate because the calculation automatically by the computer and financial statements can be generated quickly and complete because the transactions entered will be processed automatically into the financial statements.